소셜미디어 이용동기가 만족과 재방문의도에 미치는 영향 : 농촌체험마을 이용자를 중심으로 - 문영주; 정철호; Mun, Young-Ju; Jung, Chul-Ho (한국콘텐츠학회 논문지, 11(9), 2011)
This study was to explore the effect of rural tourism social media use motivation on satisfaction and revisit intention. In order to carry out the empirical study 397 survey questionnaires were collected in rural tourism social media users, PASW18 and Lisrel 8.54 statistics package were utilized for analysis of SEM The study result were as follows: first, social media use motivation had a positive influence upon satisfaction. second, social media use satisfaction had a positive influence upon revisit intention. The study suggested that need to gather extensive opinions from visitors to created and manage rural tourism village in a rational manner, and intensive research effects should be directed into the vitalizations of rural tourism villages. 본 연구는 농촌체험마을의 소셜미디어 이용동기가 만족과 재방문의도에 미치는 영향을 규명하기 위한 연구이다. 연구 분석을 위해 농촌체험마을의 소셜미디어 사이트 이용경험이 있는 397명의 표본자료가 활용되었으며 연구 분석을 위해 PASW18과 Lisrel8.54의 통계분석 도구가 활용되었다. 연구결과를 요약하면 다음과 같다. 첫째, 소셜미디어 이용동기가 만족에 유의한 영향을 미치는 것으로 분석되었다. 둘째, 소셜미디어 이용만족이 재방문의도에 유의한 영향을 미치는 것으로 검증되었다. 본 연구결과를 토대로 소셜미디어 이용 동기가 농촌 체험마을 만족과 재방문의도에 영향을 미치는 결정요인들을 분석하여 농촌체험 이용고객의 만족과 재방문을 유도할 수 있는 다양한 전략적 시사점을 제시하였다.